Natural Feed Preference Fejervarya cancrivora L. and Fejervarya limnocharis L on the West Coast of Sumatra Island - Reni susanti; Ramadhan Sumarmin (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2020)
Anuran is an animal with a short body size, wide and stiff. The head and body are united and have no tail. Ecologically, Anuran plays an important role in the food chain as secondary consumers. It is known that all types of Anuran are carnivores with a diet such as arthropods and worms. This study aims to determine the natural food preferences of F. cancrivora and F. limnocharis on the West Coast of Sumatra Island. This research is a descriptive study which was conducted in 3 stages, namely the first stage of taking Anuran in the field, the second stage of washing the stomach and the third stage of identifying the type of feed. The results showed that the type of feed that was mostly found in the stomachs of the two frogs was the Hymenoptera order from the Insect class. The overlapping niche values ​​of the two types of frogs in the village of Setara Nanggalo show a highly competitive tendency, the conclusion is that these two types of Anuran food have the same diet and are sympathetic populations.